2020
DOI: 10.1029/2020jc016866
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Remote Equatorial Winds and Local Mesoscale Eddies on the Existence of “River in the Sea” Along the East Coast of India Inferred From Satellite SMAP

Abstract: The Northern Indian Ocean (NIO) has a unique geographical setting as it is bifurcated by the Indian landmass resulting into two tropical basins viz. Arabian Sea (AS) and Bay of Bengal (BOB). These two basins are consistently influenced by the seasonally reversing monsoon wind forcing which in turn impact the surface circulation, precipitation, sea surface salinity (SSS) and exchange of water masses between the basins (Prasanna Kumar et al., 2004). The SSS is the most prominent physical parameter to distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 72 publications
2
13
0
Order By: Relevance
“…The satellites and reanalysis products extend this important result globally, thanks to their homogeneous coverage. This can be attributed to river discharges as illustrated here in the Amazon River plume and the Bay of Bengal regions (Figures 6 and 8) and previously documented in regional studies [15,46,47,69,[94][95][96]. More recently, SMOS and SMAP have been shown to reproduce well seasonal and interannual SSS variation in the mouths of major rivers [97].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The satellites and reanalysis products extend this important result globally, thanks to their homogeneous coverage. This can be attributed to river discharges as illustrated here in the Amazon River plume and the Bay of Bengal regions (Figures 6 and 8) and previously documented in regional studies [15,46,47,69,[94][95][96]. More recently, SMOS and SMAP have been shown to reproduce well seasonal and interannual SSS variation in the mouths of major rivers [97].…”
Section: Discussionsupporting
confidence: 79%
“…SMAP would even work better. It compares well with in situ SSS cross-shore sections in the BoB and reproduces a large part of the seasonal SSS variations measured at coastal stations along the RIS [18,66,69]. In October 2015 (Figure 7), SMOS LOCEAN, SMAP JPL and GLORYS captured the coastal freshening (SSS < 32 pss) seen by the TSG data at 13°N, clearly associated with the northern BoB freshening transported southward by the RIS.…”
Section: Bay Of Bengalsupporting
confidence: 76%
See 1 more Smart Citation
“…Recently, based on salinity data collected by fishermen, Chaitanya et al (2014) identified a narrow (~100 km wide) strip of low salinity water along the western BoB coast as a "river in the sea" (RIS). As a striking hydrographic feature in the BoB, the RIS has attracted attention from several investigators (Akhil et al, 2014;Fournier et al, 2017;Suneel et al, 2020). These studies confirmed the existence of the RIS from the evolution of the SSS averaged over a coastal strip box along the western BoB coast.…”
Section: Introductionmentioning
confidence: 85%
“…Li et al 10.3389/fmars.2022.1103215 example, during La Niña or negative IOD (nIOD) events, positive SSHAs were observed off the western BoB coast (Grunseich et al, 2011;Aparna et al, 2012). The positive SSHAs (cyclonic circulation anomalies) contribute to a stronger EICC during October-December (OND), causing the RIS to extend farther southward along the coast (Akhil et al, 2016;Fournier et al, 2017;Suneel et al, 2020;Li et al, 2021b). For example, the RIS extended far southward along the western BoB coast in 2016, which was attributed to the influence of the nIOD in 2016 (Fournier et al, 2017;Suneel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%